PREVENTIVE ROLE OF INTERFERON IN HEPATOCELLULAR CARCINOMA IN NON - RESPONDER HEPATITIS B AND C PATIENTS - Shah, Nazir; ., Amanullah; Shah, Mufariq; Khattak, Usman (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the preventive role of interferon in Hepatocellular carcinoma (HCC) in patients of chronic hepatitis B &C who didn't respond virologically to interferon therapy. Methodology: This comparative retrospective study was performed in the Medical Unit Hayatabad Medical Complex Peshawar from Jun2014 to April 2015. Patients of cirrhosis liver due to hepatitis C & B virus infection from the wards and hospital OPD were entered. Hbs Ag and Hepatitis C antibodies test was performed on ELISA method. Patients with liver mass on ultrasound and CT scan with raised alpha feto protein were labeled hepatocellular carcinoma were divided in the Child Class A, B or C. They were divided in to two groups, one who used interferon and the other who did not. We noted the reasons for not using interferon and the duration from the earliest evidence of Hepatitis B and C positive status to the diagnosis of HCC. Results: We collected 500 cases of cirrhosis liver due to hepatitis B & C. Sev -enty eight percent (n=390) were anti HCV while 22% (n=110) Hbs Ag positive. Fifty three percent (n=265) were male and age range was 45 to 80 years with a mean of 68 +12 years. Their average duration from the diagnosis of hepatitis B & C to cirrhosis liver or HCC was few days to 15 years with a mean of 7.5 + 7 years. Interferon was used in past by 16% (n=80) while 83% (n=415) have not and 1% (n=5) used interferon incompletely. We compared the different parameters between the two groups as shown in (table-1-2) which shows that despite not achieving sustained virological response (SVR) the treated group had significantly lower prevalence of HCC and longer duration from diagnosis to the development of HCC than the untreated cases. Conclusion: Interferon therapy can delay or prevent HCC in patients of chron-ic liver disease due to Hepatitis B and C virus even if the patient has not achieved the SVR.